2014
DOI: 10.4103/0259-1162.134493
|View full text |Cite
|
Sign up to set email alerts
|

Comparing ease of intubation in obese and lean patients using intubation difficulty scale

Abstract: Background:Difficult tracheal intubation contributes to significant morbidity and mortality during induction of anesthesia. There are divided opinions regarding ease of intubation in obese patients. Moreover, the definition of difficult intubation is not uniform; hence we have use the Intubation Difficulty Scale (IDS) to find the incidence of difficult intubation in obese patients.Aims:The primary aim of the following study is to find out the incidence of difficult intubation in obese and lean patients using I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…In non-obese patients, the sensitivity was lower. Studies addressing importance of Sternomental distance are relatively few 29 . In the study by Turkan and colleagues, younger patients (20-30 years) and male patients had longer mean sternomental distance measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In non-obese patients, the sensitivity was lower. Studies addressing importance of Sternomental distance are relatively few 29 . In the study by Turkan and colleagues, younger patients (20-30 years) and male patients had longer mean sternomental distance measurements.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that intubation of individuals with obesity was more challenging than lean counterparts 60 . Additionally, the propensity towards atelectasis in patients with obesity makes managing critical respiratory support challenging in these patients 61 .…”
Section: Obesity and Pulmonary Functionmentioning
confidence: 99%
“…all emphasise the association of elevated BMI and adverse airway events. Although obesity may impact on the ease or success of facemask ventilation, SAD insertion, laryngoscopy (modestly ) and eFONA, its most profound impact is on the speed and extent of hypoxia during routine and difficult airway management, which dramatically reduces the time during which success must be achieved . Patients with obstructive sleep apnoea are at even higher risk of increased airway difficulty and airway obstruction leading to rapid hypoxia.…”
Section: Epidemiology Of Major and Minor Airway Eventsmentioning
confidence: 99%